Development of Ethno-STEM Test Instrument to Equip Chemical Literacy on Thermochemistry Material - Khoiriyah, Fatimah; Sumarti, Sri Susilogati; Harjono (Chemistry in Education, 2025)
Chemistry education in the 21st century demands the development of chemical literacy that not only masters theoretical concepts, but also relates science to real-life contexts and scientific thinking skills. This study aims to develop a valid and reliable ethnoscience-based chemical literacy test instrument and STEM approach on thermochemical material for high school students. The development model used is 4D (Define, Design, Develop, Disseminate). The results of observations and interviews showed the need for instruments that integrate the local cultural context, especially the practice of making pottery in Klaten, with the concept of thermochemistry. Expert validation resulted in an Aiken's V value of 0.92 (high category), and the reliability test showed a value of 0.71 (good). Rasch analysis confirmed the validity of the items and the varying difficulty of the questions. This instrument is expected to improve students' chemical literacy in a contextual and meaningful way and encourage critical thinking skills